Sensitivity of grain yields to historical climate variability in India. (13th June 2019) - Davis, Kyle Frankel; Chhatre, Ashwini; Rao, Narasimha D; Singh, Deepti; DeFries, Ruth
Abstract: Fluctuations in temperature and precipitation influence crop productivity across the planet. With episodes of extreme climate becoming increasingly frequent, buffering crop production against these stresses is a critical aspect of climate adaptation. In India, where grain production and diets are closely linked, national food supply is sensitive to the effect of climate variability on monsoon grain production. Here we quantitatively examine the historical (1966–2011) relationship between interannual variations in temperature and rainfall and rainfed yield variability for five monsoon crops—rice and four alternative grains (finger millet, maize, pearl millet, and sorghum). Compared to rice, we find that alternative grains are significantly less sensitive to climate variation and generally experience smaller declines in yield under climate extremes. However, maximizing harvested area allocations to coarse grains (i.e. holding maize production constant) reduced grain production by 12.0 Mtonnes (−17.2%) under drought conditions and 12.8 Mtonnes (−18.0%) during non-drought years (non-drought). Increasing the harvested area allocated to all alternative grains (i.e. including maize) can enhance production by +39.6% (drought) and by +37.0% (non-drought). These alternative grains therefore offer promise for reducing variations in Indian grain production in response to climate shocks, but avoiding grain production shortfalls from increased alternative grains will require yield improvements that do not compromise their superior climate resilience.